Clustering of children's activity behaviour: the use of self-report versus direct measures - Saunders, Travis J; Prince, Stephanie A; Tremblay, Mark S (Université d'Ottawa | University of Ottawa, 2011)
Abstract While we concur with the objectives of the recent International Journal of Behavioural Nutrition and Physical Activity paper published by Jago and colleagues titled "Physical activity and sedentary behaviour typologies of 10-11 year olds", we feel that the results as currently presented do not support their conclusions. Though the authors created groups of children with dramatically different patterns of self-reported physical activity and sedentary behaviour, an inspection of the objectively measured accelerometry data shows little difference between the groups. Further, in at least one instance the difference between groups was of the opposite direction when using objective measures, as opposed to the self-report measures used in the published analysis. Thus, we caution the authors from making conclusions based on their self-report data, and propose that they re-analyze their data using their objectively measured data instead.